172k views
1 vote
Simplify 162x3y2−−−−−−−√ . Assume x and y are nonnegative.

User Bersh
by
6.5k points

1 Answer

0 votes

Answer:


9xy√(2x)

Explanation:

Given expression is,


√(162x^3y^2)


=(162x^3y^2)^(1)/(2)
(\because \sqrt[n]{x} =x^(1)/(n))


=162^(1)/(2)(x^3)^(1)/(2) (y^2)^(1)/(2)
(\because (ab)^m=a^mb^m)


=(81* 2)^(1)/(2) x^{3* (1)/(2)} y^{2* (1)/(2)}


=(81)^(1)/(2) (2)^(1)/(2) x^{(3)/(2)} y^{(2)/(2)}


=9(2)^(1)/(2) x^{1+(1)/(2)} y^1


=9(2)^(1)/(2) x^(1).x^{(1)/(2)} y
(\because a^(m+n)=a^m.a^n )


=9xy(2x)^(1)/(2)


=9xy√(2x)

User MRVDOG
by
4.6k points